Modelling intra- and extra-area trade substitution and exchange rate pass-through in the euro area - Alistair Dieppe; Thomas Warmedinger (European Central Bank (ECB), 2007)
The paper proposes a modelling approach for euro area goods and services trade volumes and prices on the basis of a break-down of trade data into their intra- and extra-area components. Using the evidence from the newly estimated trade equations, the paper gives new insights into two important issues. The first issue concerns the exchange-rate pass-through (ERPT) to euro area import prices. The second issue relates to substitution effects between intra- and extra-area trade. These issues are further elaborated through simulation analyses using the ECB's area-wide model (AWM). The simulations illustrate the impact of external and domestic shocks to trade in the euro area, in particular on intra- and extra-area trade. The richer dynamics from this disaggregated perspective provide additional insights and elucidate transmission channels of shocks that are not detectable from an aggregate (i.e. total trade) perspective. For instance, one interesting finding is that an appreciation of the euro has a significant downward impact on intra euro area trade.
Keywords: E31; F17; C5; 330; competitiveness and trade substitution; euro area; exchange-rate pass-through; Intra-/ extra-area trade; pricing-to-market; Internationale Wirtschaft; Interregionaler Handel; Eurozone; Exchange Rate Pass-Through; EU-Staaten